Toward providing automatic program repair by utilizing topic-based code block similarity - Jeong, Youngjun; Min, Kyeongsic; Yang, Geunseok; Lee, Jung Won; Lee, Byungjeong (Lecture Notes in Electrical Engineering, 2018)
In this paper, we propose the model for automated repair in software fault. Automated patch generation is the most important technique in these days. Genetic Programming (GP) technique is used for automatic program repair, but most of the techniques use just a source code including fault to make initial population. We propose two methods to select similar bug fixing history; using topic modeling and finding similar bugs by using code block similarity.
Keywords: Automatic programs; Bug reports; Bug-fixing; Code blocks; Initial population; Software fault; Source codes; Topic Modeling; Automatic repair; Bug report; Genetic programming; Topic modeling